Determination of a quantitative parameter to evaluate swimming technique based on the maximal tethered swimming test - Soncin, R.; Mezêncio, B.; Ferreira, J. C.; Andrade Rodrigues, S.; Huebner, R.; Cerca Serrão, J.; Szmuchrowski, L. (Sports Biomechanics, 2017)
The aim of this study was to propose a new force parameter, associated with swimmers` technique and performance. Twelve swimmers performed five repetitions of 25 m sprint crawl and a tethered swimming test with maximal effort. The parameters calculated were: the mean swimming velocity for crawl sprint, the mean propulsive force of the tethered swimming test as well as an oscillation parameter calculated from force fluctuation. The oscillation parameter evaluates the force variation around the mean force during the tethered test as a measure of swimming technique. Two parameters showed significant correlations with swimming velocity: the mean force during the tethered swimming (r = 0.85) and the product of the mean force square root and the oscillation (r = 0.86). However, the intercept coefficient was significantly different from zero only for the mean force, suggesting that although the correlation coefficient of the parameters was similar, part of the mean velocity magnitude that was not associated with the mean force was associated with the product of the mean force square root and the oscillation. Thus, force fluctuation during tethered swimming can be used as a quantitative index of swimmers` technique. ABSTRACT FROM AUTHOR